An evaluation of primary text materials in terms of the coverage of graded attainable terminal competencies - Kalam, Md. Abul; Ghosh, Sanat K. (BRAC Research and Evaluation Division (RED), 2020)
The world conference on Education for All 1990, at Jomtien, Thailand, set a new goal for the developing countries around the world to educate people of these countries with basic education. As a signatory to the declaration of this conference, Bangladesh in to impart basic education to at least 80% of school-age children by the year 2000. To serve tills purpose the Compulsory Primary Education Act was passed, and 53 terminal competencies attainable after five year primary education cycle have been identified and the text materials have also been revised accordingly. The Government of Bangladesh introduced competency-based education system in five year primary education cycle in 1992. The 'Education Watch' has undertaken a study this year 'Education Watch 2000' focusing on the learners' achievements at the end of primary level in terms of attainable terminal competencies. The particular study presented in this paper, as part of 'Education Watch 2000', focused on the evaluation of text materials (grade I to V) prepared by the NCTB in terms of the extent of coverage of graded learning continua and attainable terminal competencies specified for the achievements of learners at the end of five year primary education cycle.